The effects of agencification on the capacity of the federal inland revenue service in Nigeria - Thomas, Edoye Bless (Department of Political Studies, 2020)
The wave of Autonomous Revenue Agencies (ARA) became popular in most Sub Saharan Africa (SSA) states in the early 90s. It has been adopted as a public sector reform instrument to improve the revenue collection capacity of its various host nations. Many countries believe that the adoption of autonomy which is reducing the political control of specialized public institutions will solve corporate and administrative problems and the same time drive efficiency and effectiveness in service delivery to the public. Autonomy of revenue agencies have been at the forefront of this movement since it is the source of revenue for the whole government. Agencification which is the theoretical tool of explaining autonomy can be define as the “transfer of government activities to agency-type organization vertically specialized outside ministerial departments” (Nchukwe & Adejuwon, 2014). Agencification is closely related to the NPM movement and governments across different nationalities and continents have established agencies at arm's length from ministries to handle certain regulatory and administrative functions. The Nigerian state joined the league of nations that reformed the institutional framework of its revenue authority in 2007 by making the Federal Inland Revenue Authority (FIRS) autonomous from the Ministry of Finance. Countries such as Kenya, Ghana, Tanzania, South Africa, Uganda etc. are among some of the countries in Africa that have adopted this institutional revenue model, and each has had its own implementation experience. This research intends to study the experience of Nigeria's Federal Inland Revenue Service (FIRS) which is the nation's revenue authority after it went through its reform and to examine the effects of agencification on the operational capacity of FIRS. The idea is to find out if the autonomy of FIRS has led to improved performance and service delivery. The research mainly used qualitative method through carrying out interviews with officials of the FIRS, who were actively part of the reform implementation. Their experiences can be valuable to test the variables of agencification in FIRS. The research will also adopt other publications on the subject area, government briefs, white papers and policy documents etc. The key findings of the research was despite the whole rationale behind agencification which is to reduce the political control of executive agencies in order to function efficiently and effectively is not an area that FIRS have been able to successfully managed despite the provision of the Establishment Act. The agency responsibility to report to the National Assembly especially on areas of its budget approval and oversight function have been a challenge in the meddling of its autonomy by politicians to meet their personal or group interests. Also managing the internal stakeholders especially, the top management team of the agency will require a lot of managerial dexterity when you consider the occasional resistance to reforms that happens. There is the usual tendency for people to want to maintain how things used to be. This resistance to change is a major challenge to driving reform. Quality of leadership is also very important in driving reforms within an agency. Appointment of the Chief Executive and Board members should not be used as a tool of political patronage or settlement but rather selection of persons who are well trained and positioned to drive change within an organization.